2019
DOI: 10.1111/cas.14212
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in HPV16/18 prevalence among young women with high‐grade cervical lesions following the Japanese HPV vaccination program

Abstract: The Japanese government began a human papillomavirus (HPV) vaccination program for girls aged 12‐16 years in 2010 but withdrew its recommendation in 2013 because of potential adverse effects, leading to drastically reduced vaccination uptake. To evaluate population‐level effects of HPV vaccination, women younger than 40 years of age newly diagnosed with cervical intraepithelial neoplasia grade 1‐3 (CIN1‐3), adenocarcinoma in situ (AIS), or invasive cervical cancer (ICC) have been registered at 21 participating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 27 publications
(48 reference statements)
3
37
1
Order By: Relevance
“…In this cohort, Other hrHPV infection was most prevalent, accounting for 79.9% of hrHPV infections, and contributed to substantial cytological abnormalities as well as large proportions of CIN2/CIN3 (62.7% and 43.9%, respectively) over 3-year follow-up. With the advent of the vaccine era, prevalence of HPV16/18 infections and related CIN2+ rate are expected to decline, both in vaccinated women and unvaccinated women due to herd protection 21 , 22 . Furthermore, the eradication of HPV16/18 could lead to a relative increase in prevalence of Other hrHPV types and related CIN2+ rate 23 .…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort, Other hrHPV infection was most prevalent, accounting for 79.9% of hrHPV infections, and contributed to substantial cytological abnormalities as well as large proportions of CIN2/CIN3 (62.7% and 43.9%, respectively) over 3-year follow-up. With the advent of the vaccine era, prevalence of HPV16/18 infections and related CIN2+ rate are expected to decline, both in vaccinated women and unvaccinated women due to herd protection 21 , 22 . Furthermore, the eradication of HPV16/18 could lead to a relative increase in prevalence of Other hrHPV types and related CIN2+ rate 23 .…”
Section: Discussionmentioning
confidence: 99%
“…HPV vaccine surveillance (Unger et al 2009), while the Roche LA assay has been used in numerous studies of HPV epidemiology, screening and vaccination (Wheeler et al 2006;Kitchener et al 2011;Castle et al 2011;Markowitz et al 2013;Garland et al 2018;Matsumoto et al 2019;Onuki et al 2020). PGMY-CHUV can detect 31 individual HPV genotypes at a much lower cost (Estrade et al 2011), but requires proficient skills of laboratory work and strict quality control for the reagents and membranes.…”
Section: Discussionmentioning
confidence: 99%
“…Based on LA genotyping results, the MINT study I reported a significant reduction in cervical precancer attrib-utable to HPV16/18 among vaccinated patients from 2012 to 2017 (Matsumoto et al 2019). To monitor long-term changes in the prevalence of HPV genotypes in Japan, the MINT study II is now in progress using PGMY-CHUV.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations